Povest' o zhizni . Povest' o zhizni . Life Story . Повесть о жизни - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. In memory of the writer Konstantin Paustovsky. Featured in the program: Okudzhava, Bulat Shalvovich (Poet); Batalov, Aleksei Vladimirovich (Actor); Polenov, Fedor (Chairman of the Commission for Culture of the Supreme Soviet of the Russian Federation); Arbuzova, Galina (Screenwriter); Borshchagovskii, Aleksandr (Writer) Воспоминания о писателе Константине Паустовском. В программе участвуют: Окуджава, Булат Шалвович (Поэт); Баталов, Алексей Владимирович (Актер); Поленов, Федор (Председатель Комиссии по культуре Совета Республики Верховного Совета РСФСР); Арбузова, Галина (Сценаристка); Борщаговский, Александр (Писатель)